2005
DOI: 10.3758/bf03195323
|View full text |Cite
|
Sign up to set email alerts
|

Language switching and the effects of orthographic specificity and response repetition

Abstract: In two experiments, Greek-English bilinguals alternated between performing a lexical decision task in Greek and in English. The cost to performance on switch trials interacted with response repetition, implying that a source of this "switch cost" is at the level of response mapping or initiation. Orthographic specificity also affected switch cost. Greek and English have partially overlapping alphabets, which enabled us to manipulate language specificity at the letter level, rather than only at the level of let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 45 publications
10
76
4
Order By: Relevance
“…Grainger and Beauvillain (1987) suggested that the presence of language-specific orthographic cues in target words might help re-adjust language node activation and modulate observed switch costs. The results of Thomas and Allport (2000) show that this is not the case, although more recent research has shown that switch-costs are diminished in the presence of language-specific letters in Greek-English bilinguals (Orfanidou & Sumner, 2005). In any case, the observation of switch costs in generalized lexical decision is strong evidence against an exclusively taskschema account of the phenomenon.…”
Section: Introductionmentioning
confidence: 48%
“…Grainger and Beauvillain (1987) suggested that the presence of language-specific orthographic cues in target words might help re-adjust language node activation and modulate observed switch costs. The results of Thomas and Allport (2000) show that this is not the case, although more recent research has shown that switch-costs are diminished in the presence of language-specific letters in Greek-English bilinguals (Orfanidou & Sumner, 2005). In any case, the observation of switch costs in generalized lexical decision is strong evidence against an exclusively taskschema account of the phenomenon.…”
Section: Introductionmentioning
confidence: 48%
“…This pattern was also recently evidenced in balanced and unbalanced Spanish-Basque bilinguals using the progressive demasking task (Casaponsa et al, 2014; experiment 2). The language switch effect, where lexical decision reaction times are longer when the previous item is of a different rather than the same language, has also been reported to be weaker when the target item contains an orthographic marker (Beauvillain & Grainger, 1987;Orfanidou & Sumner, 2005). Though interesting hypotheses have been raised regarding the role of these sub-lexical orthographic markers in processing language membership information in bilinguals (van Kesteren et al, 2012), not much is yet known about sub-lexical processes per se in a second language.…”
Section: Grapheme Coding In L2: How Do L2 Learners Process New Graphementioning
confidence: 99%
“…Because multiple (usually two) languages are implemented in language switching, visual language cues are used to indicate in which language the concepts need to be produced. This procedure indicates that such a paradigm has mainly been implemented in production studies because comprehension studies generally use written words (e.g., Orfanidou & Sumner, 2005;Thomas & Allport, 2000). These words already inherently contain information about the required target language, thus eliminating the need for an additional, explicit visual cue.…”
Section: Cued Language Switchingmentioning
confidence: 99%